HUBUNGAN POLA ASUH IBU DAN PENYAKIT DIARE DENGAN KEJADIAN STUNTING PADA ANAK SEKOLAH DASAR DI SDN 01 CANDIREJO KECAMATAN UNGARAN BARAT - Winangun, Ardi; Pontang, Galeh Septiar; Indri Mulyasari (JURNAL GIZI DAN KESEHATAN, 2019)
Background :Nutritional Status Monitoring (PSG) data for 2017, the prevalence of under-five children under five reached 28.5%, in school children (5-12 years) in Indonesia reached27.7% consisting of 8.3% very short, and short 19 , 4%, in Central Java with the same time of 16.0% and in Semarang district reached 21.1%. Stunting can be caused by various factors, namely parenting and diarrheal diseases. Objective : This study aims to determine the relationship between parenting and the incidence of diarrhea with the incidence of stunting in elementary school children at SDN 01 Candirejo, District Ungaran Barat Method: The research design used descriptive and correlation is the hypothesis of chi square. conducted at the Elementary School at SDN 01 Candirejo, West Ungaran District. Sampling by total sampling. The number of respondents was 80 children from grades 1, 2 and 3. Results: Most of the authoritarian mothers' parenting were 44 (55.0), the rest were permissive 29 (36.2%) and democratic 7 (8.8%) while the incidence of diarrhea, non diarrhea 65 (81.2%) and diarrhea 15 (18 , 8%). There was no relationship between parenting with the incidence of stunting (p value = 0.115> 0.05) and there was a relationship between diarrheal disease and the incidence of stunting (p value 0.003 <0.05) of elementary school at SDN 01 Candirejo. Conclusion: There is no relationship between parenting with the incidence of stunting. There is a relationship between diarrheal diseases and the incidence of elementary school stunting at SDN 01 Candirejo Abstrak : Latar Belakang: Data Pemantuan Status Gizi (PSG) tahun 2017, prevalensi balita stunting mencapai 28,5 %, pada anak usia sekolah (5-12 tahun) di Indonesia mencapai 27,7 % yang terdiri dari 8,3 % sangat pendek, dan pendek 19,4 %, di Jawa tengah dengan usia yang sama sebesar 16,0 % dan di kabupaten semarang mencapai 21,1 %. Stunting dapat di sebabkan oleh beberapa faktor yaitu pola asuh dan penyakit diare. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara pola asuh dan kejadian diare dengan kejadian stunting pada anak SD di SDN 01 Candirejo, Kecamatan Ungaran Barat Metode : Desain penelitian yang digunakan deskriptif dan korelasi yaitu uji hipotesis kai kuadrat (chi square). dilakukan pada Sekolah Dasar di SDN 01 Candirejo Kecamatan Ungaran Barat. Pengambilan sampel dengan cara total Sampling. Jumlah responden sebayak 80 anak dari kelas 1, 2 dan 3. Hasil :sebagian besar pola asuh ibu otoriter 44 (55,0),sisanya permisif 29 (36,2 %) dan demokratis 7 (8,8 %) sedangkan kejadian diare, yang tidak diare 65 (81,2 %) dan diare 15 (18,8 %). Tidak ada hubungan antara pola asuh dengan kejadian stunting (p value= 0.115> 0.05) dan Ada hubungan antara penyakit diare dengan kejadian stunting (p value 0.003< 0.05) Sekolah Dasar di SDN 01 Candirejo. Simpulan: Tidak ada hubungan antara pola asuh dengan kejadian stunting. Ada hubungan antara penyakit diare dengan kejadian stunting Sekolah Dasar di SDN 01 Candirejo